2008
DOI: 10.1128/jvi.02472-07
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus nsp1 Suppresses Host Gene Expression, Including That of Type I Interferon, in Infected Cells

Abstract: The severe acute respiratory syndrome coronavirus (SARS-CoV) nsp1 protein has unique biological functions that have not been described in the viral proteins of any RNA viruses; expressed SARS-CoV nsp1 protein has been found to suppress host gene expression by promoting host mRNA degradation and inhibiting translation. We generated an nsp1 mutant (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
525
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(554 citation statements)
references
References 57 publications
(79 reference statements)
24
525
1
4
Order By: Relevance
“…These findings highlight the importance of vhs in controlling host immune responses to HSV. Likewise, Narayanan et al showed that SARS-CoV nsp1 suppresses host gene expression in infected cells, including the expression of the type I IFN gene and ISGs like those encoding beta interferon (IFN-␤), ISG15, and ISG56 (9). It has also been reported that SARS-CoV nsp1 plays a role in the interruption of the IFN signaling pathway by decreasing the phosphorylation of STAT1 and is necessary for efficient viral growth in the human lung epithelial cell line Calu-3 (10).…”
Section: Virus-induced Host Protein Shutoff Is Considered To Be a Majmentioning
confidence: 99%
“…These findings highlight the importance of vhs in controlling host immune responses to HSV. Likewise, Narayanan et al showed that SARS-CoV nsp1 suppresses host gene expression in infected cells, including the expression of the type I IFN gene and ISGs like those encoding beta interferon (IFN-␤), ISG15, and ISG56 (9). It has also been reported that SARS-CoV nsp1 plays a role in the interruption of the IFN signaling pathway by decreasing the phosphorylation of STAT1 and is necessary for efficient viral growth in the human lung epithelial cell line Calu-3 (10).…”
Section: Virus-induced Host Protein Shutoff Is Considered To Be a Majmentioning
confidence: 99%
“…Secreted IFN binds to the IFN receptor and activates a JAK/STAT signalling pathway, upregulating the expression of a subset of genes that impede virus replication (Randall & Goodbourn, 2008). However, many viruses have evolved mechanisms to circumvent the IFN response (Blakqori et al, 2007;Jennings et al, 2005;Kopecky-Bromberg et al, 2007;Narayanan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Secreted IFN binds to the IFN receptor and activates a JAK/STAT signalling pathway, upregulating the expression of a subset of genes that impede virus replication (Randall & Goodbourn, 2008). However, many viruses have evolved mechanisms to circumvent the IFN response (Blakqori et al, 2007;Jennings et al, 2005;Kopecky-Bromberg et al, 2007;Narayanan et al, 2008).Porcine reproductive and respiratory syndrome virus (PRRSV), the causative agent of porcine reproductive and respiratory syndrome, is a small enveloped, singlestranded, positive-sense RNA virus belonging to the family Arteriviridae within the order Nidovirales (Meulenberg, 2000). The genome is about 15.4 kb and contains at least nine ORFs.…”
mentioning
confidence: 99%
“…In order to combat the antiviral effects of IFN-a/ b, many viruses, such as coronavirus, have evolved distinct strategies to inhibit IFN signalling pathways for their survival (Haller & Weber, 2007). Human coronavirus, severe acute respiratory syndrome coronavirus (SARS-CoV), encodes at least six innate immune antagonists, including non-structural protein 1 (nsp1) (Narayanan et al, 2008), the papainlike protease domain in nsp3 (Devaraj et al, 2007), nucleocapsid protein (Kopecky-Bromberg et al, 2007;Lu et al, 2011), membrane protein (Siu et al, 2009) and the products of ORF6 and ORF3b (Kopecky-Bromberg et al, 2007). Our previous work found that human NL63 CoV (HCoV-NL63) (van der Hoek et al, 2005) also encodes a papain-like protease, termed PLP2, which has deubiquitinase (DUB) activity and antagonizes IFN induction (Chen et al, 2007;Clementz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%